2017
DOI: 10.17533/udea.penh.v18n2a07
|View full text |Cite
|
Sign up to set email alerts
|

Perspectivas del pensamiento ecológico que han influenciado el campo alimentario y nutricional

Abstract: Cómo citar este artículo: Cadavid MA, Giraldo LF. Perspectivas del pensamiento ecológico que han influenciado el campo alimentario y nutricional. Perspect Nutr Humana. 2016;18:225-36. DOI:10.17533/udea.penh.v18n2a07 DOI:10.17533/udea.penh.v18n2a07 Perspectivas del pensamiento ecológico que han influenciado el campo alimentario y nutricional ResumenIntroducción: la nutrición humana trasciende aspectos biológicos y está integrada por aspectos sociales, políticos, históricos, ambientales, económicos y cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Ivanovic and collaborators [45] found that the differences in IQ among Chilean high school students were mainly due to malnutrition in childhood. According to Cadavid Castro [46], it is increasingly clear that the quantity and quality of nutrients received by the child are directly related to their cognitive potential and their mental and emotional health, in addition to reflecting on adult brain functions and their eventual decline with age. Childhood is the crucial phase in which many health-related behaviors are shaped [47], and a child does not choose the environment in which he lives, much less has the skill and knowledge necessary to choose a diet or exercise.…”
Section: The Importance Of An Integrative Approach Of Child Developmentmentioning
confidence: 99%
“…Ivanovic and collaborators [45] found that the differences in IQ among Chilean high school students were mainly due to malnutrition in childhood. According to Cadavid Castro [46], it is increasingly clear that the quantity and quality of nutrients received by the child are directly related to their cognitive potential and their mental and emotional health, in addition to reflecting on adult brain functions and their eventual decline with age. Childhood is the crucial phase in which many health-related behaviors are shaped [47], and a child does not choose the environment in which he lives, much less has the skill and knowledge necessary to choose a diet or exercise.…”
Section: The Importance Of An Integrative Approach Of Child Developmentmentioning
confidence: 99%